The risk of suprascapular and axillary nerve injury in reverse total shoulder arthroplasty: An anatomic study. Issue 10 (October 2017) - Leschinger, Tim; Hackl, Michael; Buess, Eduard; Lappen, Sebastian; Scaal, Martin; Müller, Lars Peter; Wegmann, Kilian
Abstract: Purpose: Implantation of a reverse total shoulder arthroplasty (rTSA) places the axillary and suprascapular nerves at risk. The aim of this anatomic study was to digitally analyse the location of these nerves in relation to bony landmarks in order to predict their path and thereby help to reduce the risk of neurological complications during the procedure. Methods: A total of 22 human cadaveric shoulder specimens were used in this study. The axillary and suprascapular nerves were dissected, and radiopaque threads were sutured onto the nerves without mobilizing the nerves from their native paths. Then, 3D X-ray scans of the specimens were performed, and the distance of the nerves to bony landmarks at the humerus and the glenoid were measured. Results: The distance of the inferior glenoid rim to the axillary nerve averaged 13.6 mm (5.8–27.0 mm, ±5.1 mm). In the anteroposterior direction, the distance between the axillary nerve and the humeral metaphysis averaged 8.1 mm (0.6–21.3 mm, ±6.5 mm). The distance of the glenoid centre to the suprascapular nerve passing point under the transverse scapular ligament measured 28.4 mm (18.9–35.1 mm, ±3.8 mm) in the mediolateral direction and 10.8 mm (−4.8 to 25.3 mm, ±6.1 mm) in the anteroposterior direction. The distance to the spinoglenoid notch was 16.6 mm (11.1–24.9 mm, ±3.4 mm) in the mediolateral direction and −11.8 mm posterior (−19.3 to −4.7 mm, ±4.7 mm) in the anteroposterior direction. Conclusions: Implantation of rTSA components endangers the axillary nerve because of its proximity to the humeral metaphysis and the inferior glenoid rim. Posterior and superior drilling and extraosseous screw placement during glenoid baseplate implantation in rTSA place the suprascapular nerve at risk, with safe zones to the nerve passing the spinoglenoid notch of 11 mm and to the suprascapular notch of 19 mm.